Implementation of Live Forensic Method on Fusion Hard Disk Drive (HDD) and Solid State Drive (SSD) RAID 0 Configuration TRIM Features - Desti Mualfah; Rizdqi Akbar Ramadhan; Muhammad Arrafi Arrasyid (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2024)
One of the solutions used for access speeds is to maximize non-volatile storage functions by a conventional Hard Disk Driver with Solid State Drive that has the TRIM architecture using the Redundant Array of Inexpensive Disks 0 configuration or the commonly known RAID 0. RAID 0 is a stripping technique that has the highest speed among other RAID configurations. However, this configuration has a disadvantage in that when there is damage to one of the storage disks all the data will be corrupted and lost. It's becoming one of the challenges in digital forensic investigation when it comes to computer crime. Furthermore, this research uses experimental practices using live forensic methods to perform analysis and examination against the merger of HDD and SSD configuration RAID 0 TRIM features. The expected is an overview of the characteristics of recovery capability to find out the authenticity integrity values of files that have been lost or permanently deleted on both TRIM SSD functions disable and enable. Furthermore, this research is expected to be a solution for the experimental and practical investigation of computer crime especially in Indonesia given the increasing development of technology that is directly compared with the rise in computer crime.